Friedel–Crafts Alkylation of Indoles with Aldehydes/Ketones Catalyzed by Bromodiarylethene-Based Photoacid Generators - Zakharov, Alexey V.; Timofeeva, Sofia M.; Shirinian, Valerii Z. (Synthesis, 2024)
Diarylethenes (DAEs) with a bromine atom at the ring-closing position catalyze C–C bonding reactions induced by UV or sunlight. Upon photo-irradiation, bromodiarylethenes undergo 6π-electrocyclization (6π-EC), followed by the release of an acid species that catalyzes the double Friedel–Crafts addition of indoles to aldehydes and isatins to form the corresponding triarylmethanes and 3,3′-diarylindolin-2-ones. This protocol is applicable to a wide spectrum of aldehydes and isatins, as well as chalcones as electrophiles. Acid or oxidant-sensitive functional groups, such as ferrocene, 4-methoxyphenyl, thiophene, pyrrole are tolerated. Mechanistic studies show that light is needed to initiate the reaction.
Keywords: aldehydes; catalysis; diarylethenes; diindolylmethanes; Friedel–Crafts alkylation; Lewis acid; photoacid generators; photochemistry